Evaluasi Sifat Mekanik Sambungan Saw Material BS 1501 223 490B Melalui Uji Destruktif - Hendra Susilo; Putra Pratama; Suardi; Fadlah K. Sinurat (Jurnal Nasional Teknologi Komputer, 2025)
his study aims to evaluate the mechanical properties of welded joints produced using the Submerged Arc Welding (SAW) method on BS 1501 223 490B steel material. The evaluation was carried out through destructive testing, including tensile test, bend test, and Charpy impact test. The tensile test revealed a maximum tensile strength of 584.39 N/mm² on the All Weld specimen, with an elongation of 26.23%. In the Transverse test, fracture occurred in the base metal, indicating that the weld joint had superior quality compared to the parent material. The bend test on both Face Bend and Root Bend specimens showed visually "Satisfactory" results, with maximum stress reaching 2,122.55 N/mm². The Charpy V-notch impact test indicated an average absorbed energy of 109.98 Joules at room temperature, demonstrating good toughness under impact loading. The results confirm that welded joints produced by the SAW method on BS 1501 223 490B steel exhibit excellent strength, ductility, and toughness, making them suitable for structural and high-pressure applications. This study reinforces the effectiveness of the SAW method in producing high-quality joints in the metal fabrication industry.